An advanced course in modern nuclear physics - Lozano, M (Springer, 2013)
This is a tutorial introduction to the field of modern nuclear physics. It should bridge the gap between standard textbook material and research literature for those who intend to work in any of the disciplines where nuclear science and technology should an important role in the future.